2021
DOI: 10.1103/physrevapplied.15.034009
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the Half-Metallicity at the Interfaces in Co2MnSi -Based All-Full-Heusler-Alloy Spintronic Devices

Abstract: Based on first-principles methods, we demonstrate that it would be possible to design efficient all-full-Heusler-alloy-based spintronic devices associating Co 2 MnSi electrodes and nonmagnetic full-Heusler-alloy spacers selected to preserve the half-metallicity of Co 2 MnSi up to the interface atomic layers. We focus on the Co 2 MnSi/Fe 2 TiSi magnetic tunnel junction, compare the stability range of its different interface terminations, and show that the half-metallicity of the Fe 2 /MnSi-terminated interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 55 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…While many theoretical studies on the electronic band structures and magnetic properties of all-Heusler stacks have been reported [19,[53][54][55][56][57][58][59][60][61][62][63][64], there has only been a few experimental studies [45,46,65,66]. In particular, for the emergence of unique physical properties expected theoretically, it is necessary to precisely control the structural ordering in not only the bulk region but also the interfacial region of all-Heusler stacks.…”
Section: Resultsmentioning
confidence: 99%
“…While many theoretical studies on the electronic band structures and magnetic properties of all-Heusler stacks have been reported [19,[53][54][55][56][57][58][59][60][61][62][63][64], there has only been a few experimental studies [45,46,65,66]. In particular, for the emergence of unique physical properties expected theoretically, it is necessary to precisely control the structural ordering in not only the bulk region but also the interfacial region of all-Heusler stacks.…”
Section: Resultsmentioning
confidence: 99%
“…As in reference [50,64], the surface energy γ S of an X 2 YZ's symmetric slab with two identical surfaces S could be written as:…”
Section: Data Availability Statementmentioning
confidence: 99%
“…In an early study on all-Heusler alloy MTJ Co 2 CrSi/Cu 2 CrAl/Co 2 CrSi, spin-polarization of nearly 100% could be reserved in the ferromagnetic layer ( Bai et al, 2012 ). In 2021, Pradines et al (2021) studied two all-Heusler alloy MTJs, Co 2 MnSi/Fe 2 TiSi (001) and Co 2 MnSi/Fe 2 VAl (001), and showed that the half-metallicity of the Fe 2 /MnSi-terminated interface even withstands atomic intermixing. In 2022, Feng et al (2022) also studied the all-Heusler alloy MTJ CoFeTiSi/Fe 2 TiSi/CoFeTiSi system, and a high TMR ratio of 2.4 × 10 8 % was predicted.…”
Section: Introductionmentioning
confidence: 99%